A computational study on the reaction mechanism of neutral phenol with formaldehyde in aqueous solution. (June 2016) - Cao, Ming; Li, Taohong; Wu, Zhigang; Liang, Jiankun; Xie, Xiaoguang; Du, Guanben
The reaction mechanism of neutral phenol with formaldehyde in aqueous solution was studied theoretically by using the GGA-PW91/DNP+COSMO method. In previous studies, it was found that the water molecules can mediate proton transfer from nitrogen to oxygen, but the results of this study show that water molecules can also catalyse proton transfer from carbon to oxygen. With the mediation of water, the energy barriers were greatly lowered. The calculated energy barriers indicate that the para -position of phenol has higher reactivity than the ortho -position. The reaction occurs in a concerted mechanism. However, the process exhibits asynchronous characteristics, particularly the C–C bond formation precedes the proton transfer and the proton transfer from water molecules to the carbonyl oxygen is ahead of proton abstraction from the benzene ring.